QORADARYO GIDROBIONTLARI FAUNASI VA EKOLOGIYASI - Izzatullayev , Zuvayd; Bolotov, I. N; Boymurodov, X.T.; Egamqulov, A. N.; Aliyev, B.X.; Mirzamurodov, O.X. (Actual problems and prospects of the study of the fauna, 2024)
The distribution of 14 species of hydrabionts belonging to the families Unionidae, Corbiculidae, Lymnaeidae, Physidae, Planorbidae, and Hirudinidae, Actacidae was studied in the Talig'ulon region of Karadarya. We found out that 9 hydrabionts are distributed in the water ecosystems of the Narpai district of Karadarya, with a low number of hydrabionts compared to the higher part of the species composition.